Effect of smoking on some biochemical parameters in serum of blood - Khalid. Ah. Ha. Al-saedy; Buthina Abd. Al-taee (Tikrit Journal of Pure Science, 2023)
The present study was conducted to determine the changes in a number of biochemical parameters associated with smoking. It pulled the 50 blood samples from two groups, the first group included 35 smoking volunteers while the second group included 15 non-smoking volunteers who represented the control group. The results showed that the group of smokers has risen significantly (P<0.05) in the Malondialdelyde and radical of peroxy nitrate and get significant decrease in the concentration of Glutathione and Ceruloplasmin and effectiveness of Super oxide dismutase and aryl esterase enzyme compared with the control group. We conclude from this study that smoking has a negative effect on the antioxidants in the blood serum was accompanied by an increase in the level of Malondialdelyde and peroxy nitrate radical This indicate incidence of oxidative stress which accompany smoking phenomena.